Filipino attitude and perception on Subscriber Identity Module (SIM) Card Registration Act - Aera L. Diaz; Romano M. Balbacal (International Review of Social Sciences Research)
The SIM Card Registration Act, a legislative initiative in the Philippines, mandates the registration of Subscriber Identity Module (SIM) cards to enhance security, monitor mobile phone usage, and curb crimes such as fraud, terrorism, and phishing. This phenomenological study explores the attitude and perceptions of individuals on the implementation of the Act, with a focus on how it impacts their sense of security, privacy, and everyday mobile phone use. Semi-structured interviews were conducted with 15 participants, aged 16 to 64, from the different barangays in San Pablo City, Laguna, Philippines. Data were analysed thematically, capturing participants' unique perspectives on the benefits and risks associated with the Act. The findings reveal that while participants acknowledged the Act's potential to prevent crimes and phishing, concerns about personal data security and the possibility of identity theft were prevalent. Participants’ attitudes toward the Act were shaped by their experiences with mobile phone technology and privacy concerns, with older respondents expressing heightened sensitivity to data privacy. These insights underscore the need for more robust security measures in the registration process to enhance public trust. The study concludes with recommendations to improve user experience and safeguard personal information, offering a foundation for policy refinements and further research.